FOXTAIL MILLET ( FETTUCINI JEWAWUT ) WITH BALI SPICE CHICKEN AS A FUSION FOOD - Sugiyono, Riki Ramadhon Pratama (Prosiding Pendidikan Teknik Boga Busana, 2020)
This final project aims to: 1) Foxtail millet product development, 2) knowing the community's acceptance of Foxtail millet products. The type of research used in making this product is Research and Development (R & D) with the development model of Define, Design, Develop, Disseminate (4D). Define is the stage of determining the reference recipe, Design is the stage of product development, Develop is the product validation stage, Disseminate is the stage of implementing the product that has gone through the validation stage and exhibited at the exhibition. The place and time of the study were at the Food Laboratory of the Department of Food and Clothing Engineering Education, Faculty of Engineering, Yogyakarta State University held on February 1st to March 27th 2019. The test material was a sample of each product, while testing instruments were experimental forms, validation forms I and II, panelist sensory test forms, and preferred test forms during exhibitions with data analysis techniques. The results obtained from this product research are: 1) the right recipe for Foxtail Millet products is a product that replaces wheat flour with millet flour as much as 30% by using the one stage method namely liquid and dry ingredients mixed and stirred together until smooth, then packed using carton cups. 2) Community acceptance of Foxtail Millet products with a total of 3,687 with a highly favored category from the data shows that the product is acceptable to the public. Keywords: Millet flour, Foxtail Millet